(untitled) (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
ESG values have transformed into strategic priorities for companies striving to adhere to the principles of Sustainable Development and aiming to be responsible, resilient, and progressive. This transformation is especially critical for agribusinesses in Ukraine, which face numerous challenges due to ongoing military aggression and must ensure their survival and sustainability. It is imperative to replace conservative management models and outdated agricultural technologies with modern approaches. A management framework based on three primary components ‒ environmental (E), social (S), and corporate governance (G) ‒ is essential for addressing contemporary challenges. It has been established that the key prerequisites for implementing ESG strategies in agribusiness include global trends in Sustainable Development and domestic Ukrainian factors such as economic, political-legal, social, ecological, scientific-technical, and cultural conditions. The necessity of implementing ESG strategies stems from the economic benefits they provide to agribusinesses, including increased competitiveness and access to investments and financing. Compliance with international standards through ESG strategies enhances trust among foreign partners and investors, thereby strengthening the global market position of Ukrainian agribusinesses. The adoption of ESG strategies is also driven by the need to adapt to climate change and mitigate its impact on agriculture, alongside a heightened responsibility for resource usage and environmental impacts. The challenges posed by military aggression have acted as a catalyst for socially-oriented initiatives within ESG strategies, helping agribusinesses support local communities, maintain social stability, and build trust among the population. Additionally, the growing consumer demand for eco-friendliness necessitates enhanced social responsibility from Ukrainian agribusinesses. A proposed step-by-step ESG strategy plan aims to enhance post-war recovery and growth, focusing on innovation to boost production efficiency and reduce environmental harm. Integrating ESG practices can minimize risks, improve adaptability, and ensure sustainable development during Ukraine’s recovery.